The Effect of Boycotts on Stock Volatility: An Event Study - Nur Hishaly GH; Muh Ginanjar; Muhammad Nurhadi N; Wafiq Asizah (Jurnal Hukum Ekonomi Syariah, 2024)
This research investigates the impact of the MUI (Majelis Ulama Indonesia) fatwa number 83 of 2023, which calls for a boycott of products affiliated with Israel, on the stock performance of targeted companies. The primary objective is to analyze market reactions to the fatwa announcement, employing an event study approach to measure abnormal stock returns before and after the announcement. Data was collected using purposive sampling from companies identified as boycott targets, including PT. Fast Food Indonesia Tbk, PT. Map Boga Adiperkasa Tbk, PT. Sarimelati Kencana Tbk, and PT. Unilever Indonesia Tbk. The findings reveal a significant decline in abnormal returns for the targeted companies following the fatwa announcement, indicating a negative investor reaction that led to increased selling activity. This study highlights the strategic implications for companies facing boycotts, emphasizing the need for risk mitigation strategies in response to consumer sentiment. Additionally, it suggests further research incorporating qualitative methods to delve deeper into investor behavior regarding such fatwas.